Cost Optimisation for Wheelchair Redesign - Bellal, Salah-Eddine; Leila-Hayet Mouss; Sahnoun, M’hammed; Messaadia, Mourad (1st International Conference On Cyber Management And Engineering (CyMaEn), 26-28 May, 2021)
Requirements of users in developing countries differ from those of developed countries. This difference can be seen through wheelchair displacement in infrastructures that don’t meet international standards. However, developing countries are obliged to purchase products from developed countries that don’t necessarily meet all user’s requirements. The modification of these requirements will generate disruption on all the supply chain. This paper proposes a model for optimising the cost of requirement modification on the supply chain and seeks to evaluate the introduction of a new requirement on an existing product/process. This model is adapted to the redesign and development of products, such as wheelchairs, satisfying specific Algerian end-user requirements.